2014
DOI: 10.1093/jnci/dju314
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Survival After Ovarian Cancer: Results From the Women's Health Initiative

Abstract: Our results suggest that overall higher prediagnosis diet quality may protect against mortality after ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 45 publications
7
53
1
2
Order By: Relevance
“…The proportion of deaths from causes other than ovarian cancer was small in the studies with data on cause-specific mortality, as has been reported in other ovarian cancer case series (18). It is likely that the majority of deaths occurring in the first five years after diagnosis were due to ovarian cancer and so any misclassification will have been minimal.…”
Section: Discussionmentioning
confidence: 46%
“…The proportion of deaths from causes other than ovarian cancer was small in the studies with data on cause-specific mortality, as has been reported in other ovarian cancer case series (18). It is likely that the majority of deaths occurring in the first five years after diagnosis were due to ovarian cancer and so any misclassification will have been minimal.…”
Section: Discussionmentioning
confidence: 46%
“…The second study, by Dolocek and colleagues, featured 341 women with ovarian cancer from a case-control study conducted in Cook County, IL, among whom 176 died [56]. Consistent (continued on next page) [57]. This study reported lower risks of dying for women with the highest overall diet quality (HR = 0.73, 95% CI = 0.55-0.97), but no significant association with any of the specific components of the HEI-2005.…”
Section: Dietmentioning
confidence: 99%
“…The WHO Healthy Diet Indicator (HDI), based on recommended nutrient cutoffs, is associated with improved life expectancy (18). In many instances, dietary pattern-cancer associations have been found that were not evident when investigating single foods or nutrients (19)(20)(21)(22)(23)(24). These findings and the need for additional dietary pattern research were emphasized by the 2015 US Dietary Guidelines Advisory Committee (1).…”
Section: Introductionmentioning
confidence: 99%